2012
DOI: 10.5005/jp-journals-10006-1202
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus Vulgaris with Pregnancy

Abstract: Pemphigus vulgaris is an autoimmune bullous dermatosis affecting skin and mucous membrane.2 It affects all races and both sexes equally. It is common during the 5th and 6th decade of life.3 It is exceedingly rare in pregnancy 5 and is associated with increased maternal morbidity and poor neonatal outcome. 4 We do report a case of pemphigus vulgaris with pregnancy. She conceived during the active phase of the disease and treated with steroids throughout pregnancy. She delivered a live preterm, appropriate for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Five (13.5%) neonates were born before 37 weeks of gestational age. Reasons for premature delivery included premature rupture ( n = 3), 15–17 placenta previa ( n = 1), 18 and placental insufficiency ( n = 1) 12 . One (2.7%) neonate was born after 43 weeks of gestational age, 19 and one (2.7%) died of miscarriage 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five (13.5%) neonates were born before 37 weeks of gestational age. Reasons for premature delivery included premature rupture ( n = 3), 15–17 placenta previa ( n = 1), 18 and placental insufficiency ( n = 1) 12 . One (2.7%) neonate was born after 43 weeks of gestational age, 19 and one (2.7%) died of miscarriage 9 .…”
Section: Resultsmentioning
confidence: 99%
“…TA B L E 3 Data on pregnant patients with pemphigus vulgaris onset during the postpartum period. 3 premature rupture, 15,16 1 placenta previa, 18 1 placental insufficiency, 17 1 prolonged pregnancy, 19 1 miscarriage 9 3 still birth 7 , 1 premature rupture 21 , 1 simple premature delivery 22 1 fetal distress 4 2 reported "small for date" 51 This study presents two cases of pemphigus vulgaris in women who achieved remission before but experienced a relapse during pregnancy. Although the impact on the fetus is limited, these cases offer insights into the potential relapse in patients who attained remission before pregnancy.…”
Section: Referencementioning
confidence: 99%
“…2 It is common in eastern countries like India, Malaysia, and China and rare in western world. 3 A recent study from the United Kingdom has suggested an incidence of PV of 0.68 cases per 100,000 persons per year. 4 Genetic factors and psychological stress play an important role in its predisposition.…”
Section: Introductionmentioning
confidence: 99%